Seed source has variable effects on species, communities, and ecosystem properties in grassland restorations - Carter, Daniel L.; Blair, John M. (My University, 2013)
Research to date regarding the relative advantages of local versus non-local sources of plant material for restoration has produced equivocal results. This research has typically focused on the performance of individual species at individual locations and without addressing higher order community and ecosystem properties. We investigated the effects of seed source (local, non-local, and mixed-source treatments) on species, community, and ecosystem properties under a range of environmental conditions using reciprocal common gardens at locations in three states (Nebraska, Kansas, and Oklahoma). In order to mimic the restoration of grassland vegetation under realistic conditions where multiple species interact with one another during establishment, we seeded twelve species together between December, 2009 and January, 2010, and assessed responses in 2010, 2011, and 2012. Both common garden location and seed source affected the establishment of individual species (measured as species-specific biomass), but responses were not consistent among species. No seed source had a consistent advantage across all sites or across all species. In a few cases, the local source was most productive for a particular species at one location, but no species showed a consistent local advantage across locations or years. Rather, in two out of three species that exhibited a local advantage at one location, the same source was also the most productive at a non-local site. Community structure and species richness differed among locations in all years, but source did not significantly affect seeded species richness, and source only affected community structure in 2011. Despite source effects on individual species and community structure, seed source had no significant effects on the combined productivity of seeded species. These results do not support the targeted use of local sources when the establishment of sown species and primary productivity are restoration objectives. Using mixed-source species mixtures may increase chances of restoration success, given the idiosyncrasy of individual species' responses among locations and potential site-specific environmental changes likely to occur in the future.
Keywords: Common garden; Seed transfer zone; Tallgrass; Managed relocation plant; Genetic diversity; Local adaptation